2020
DOI: 10.2147/idr.s240162
|View full text |Cite
|
Sign up to set email alerts
|

<p>Management of Acute Bacterial Meningitis in Children</p>

Abstract: Acute community-acquired bacterial meningitis (ABM) in children continues to have high rates of neurological morbidity and mortality despite the overall declining rates of infection attributed to the use of vaccines and intrapartum Group B Streptococcus prophylaxis. Prompt diagnosis and early antibiotic therapy are crucial and should not be delayed to obtain cranial imaging. Differentiating bacterial from viral meningitis continues to be a clinical dilemma especially in patients with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 88 publications
1
53
0
5
Order By: Relevance
“…In the microbiologically confirmatory analysis of bacterial meningitis, CSF white blood cells tallies of more than 21 cells/ mm 3 had an affectability of 79% and explicitness of 81%. The concentrations of CSF glucose and protein varied from 0 to 198 mg/dL (median, 20 mg/dL) and 0.4 to 19.6 g/L (median, 2.7 g/L), respectively; microbiological culture-demonstrated bacterial meningitis was not analyzed precisely by cerebrospinal fluids protein or glucose (Alamarat et al 2020;Johansson et al 2015 andPanuganti 2017).…”
Section: Positivity Ratementioning
confidence: 99%
“…In the microbiologically confirmatory analysis of bacterial meningitis, CSF white blood cells tallies of more than 21 cells/ mm 3 had an affectability of 79% and explicitness of 81%. The concentrations of CSF glucose and protein varied from 0 to 198 mg/dL (median, 20 mg/dL) and 0.4 to 19.6 g/L (median, 2.7 g/L), respectively; microbiological culture-demonstrated bacterial meningitis was not analyzed precisely by cerebrospinal fluids protein or glucose (Alamarat et al 2020;Johansson et al 2015 andPanuganti 2017).…”
Section: Positivity Ratementioning
confidence: 99%
“…The causative pathogens of bacterial meningitis in children vary widely according to age, geographic region, or the patient’s underlying medical condition [ 20 , 21 ]. Although the overall incidence dropped after the introduction of widespread pneumococcal vaccination, S. pneumoniae remains the most common cause of pediatric bacterial meningitis [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we had a large sample size to perform an overall analysis from the NHIRD of Taiwan, our study has some limitations. First, several previous studies have demonstrated that the annual incidence of bacterial meningitis in children and causative pathogens varied with age [ 20 , 21 , 22 , 25 ]. Except for H. influenzae (ICD-9-CM codes 3200), S. pneumoniae (ICD-9-CM codes 3201), and Escherichia coli (ICD-9-CM codes 320.82), not all of the causative pathogens had ICD-9-CM codes that could be recorded in the NHIRD nationwide population-based database.…”
Section: Discussionmentioning
confidence: 99%
“…Delays in antibiotic treatment >6 hours after presentation are associated with adverse outcomes. 14 A retrospective review of 123 cases of adult acute bacterial meningitis found that the risk of death in patients was 8.4 times higher when antibiotics were delayed >6 hours after presentation, with delay in antibiotic administration for CT and LP being a common cause of delay. 15 The Infectious Disease Society of America recommends that at least blood cultures should be obtained before empiric antibiotics are administered if an LP will be delayed.…”
Section: Questions/discussion Points Partmentioning
confidence: 99%